Early rabbinic writings - Maccoby, Hyam 1924-2004 (Cambridge Univ. Press, 1988)
Rabbinic texts are often cited in New Testament and Old Testament studies, but hitherto there has been no easy way for a student to grasp the scope and variety of the relevant rabbinic writings. This book introduces the student to the full range of the early rabbinic writings, with a thorough introduction and notes, so that both a bird's eye view of the literature as well as close aquaintance with typical and important texts can be obtained. This will enable the reader to embark on further study with a clearer orientation. The book also aims to correct many mistaken views about rabbinic Judaism arising from outdated conceptions of the relation between Christianity and Judaism
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Erscheinungsjahr des E-Books: 2010
Keywords: Talmud; Geschichte 200 v. Chr.-200; Rabbinical literature / History and criticism; Rabbinical literature / Translations into English; Rabbinische Literatur; Einführung